The Relationship Discipline Learning And Way Of Learning Method With Biology Learning Outcomes Based On The Academic Ability Of Class XI Science Students In SMA Negeri 6 Academic Year 2018/2019 - SARI, CINDY PERMATA; Mellisa, Mellisa (Universitas PGRI Sumatera Barat, 2019)
The purpose of this research was to determined whether there is a relationship of discpiline learning and way of learning method with biology learning outcomes based on the academic ability of class XI science students. Analysis of the data in this study using correlation analysis Person Product Moment. The results showed that for high academic, learning discipline (X1), the learning method (X2), with biology learning outcomes (Y) there is a high relationship (0,626). For medium academic, learning discipline (X1) the learning method (X2) with biology learning outcomes (Y) there is a medium relationship (0,509). For low academic, learning discipline (X1) the learning method (X2) with biology learning outcomes (Y) there is a medium relationship (0,523). Indicates a significant between way of learning discipline and learning method with result of biology study based on the academic ability of class XI science student.